Carrying Capacity and Colonization Dynamics of Curvibacter in the Hydra Host Habitat - Wein, Tanita; Dagan, Tal; Fraune, Sebastian; Bosch, Thomas C. G.; Reusch, Thorsten B. H.; Hülter, Nils F. (Frontiers in Microbiology, 2018)
Most eukaryotic species are colonized by a microbial community – the microbiota – that is acquired during early life stages and is critical to host development and health. Much research has focused on the microbiota biodiversity during the host life, however, empirical data on the basic ecological principles that govern microbiota assembly is lacking. Here we quantify the contribution of colonizer order, arrival time and colonization history to microbiota assembly on a host. We established the freshwater polyp Hydra vulgaris and its dominant colonizer Curvibacter as a model system that enables the visualization and quantification of colonizer population size at the single cell resolution, in vivo, in real time. We estimate the carrying capacity of a single Hydra polyp as 2x105 Curvibacter cells, which is robust among individuals and time. Colonization experiments reveal a clear priority effect of first colonizers that depends on arrival time and colonization history. First arriving colonizers achieve a numerical advantage over secondary colonizers within a short time lag of 24 hours. Furthermore, colonizers primed for the Hydra habitat achieve a numerical advantage in the absence of a time lag. These results follow the theoretical expectations for any bacterial habitat with a finite carrying capacity. Thus, Hydra colonization and succession processes are largely determined by the habitat occupancy over time and Curvibacter colonization history. Our experiments provide empirical data on the basic steps of host-associated microbiota establishment – the colonization stage. The presented approach supplies a framework for studying habitat characteristics and colonization dynamics within the host-microbe setting.